Effects of vibro-milling on relaxor ferroelectric behavior and phase transition of lead-free Ba(Zr0.25Ti0.75)O3ceramics - C. Kruea-In (2018)
Lead-free Ba(Zr0.25Ti0.75)O3ceramics were synthesized from powders prepared by a conventional mixed oxide and vibro-milling method to investigate the phase transition, dielectric response, and ferroelectric properties of the prepared samples. Compared to a conventional sample, the samples prepared by the vibro-milling method showed a higher dielectric constant at the ferroelectric-to-paraelectric transition temperature. The vibro-milling method also produced a stronger frequency dependence on the dielectric constant. To confirm the dielectric properties and phase transition behavior, ferroelectric hysteresis measurements were carried out in the temperature range -40°C to 80°C. The microstructural properties of the samples were investigated and the results were then correlated with the characteristics of the milled and calcined powder as well as the grains of the ceramics. © 2010 Taylor & Francis.